2018
DOI: 10.1177/1073274818757418
|View full text |Cite
|
Sign up to set email alerts
|

Dose Escalation of Vitamin D3 Yields Similar Cryosurgical Outcome to Single Dose Exposure in a Prostate Cancer Model

Abstract: Vitamin D3 (VD3) is an effective adjunctive agent, enhancing the destructive effects of freezing in prostate cancer cryoablation studies. We investigated whether dose escalation of VD3 over several weeks, to model the increase in physiological VD3 levels if an oral supplement were prescribed, would be as or more effective than a single treatment 1 to 2 days prior to freezing. PC-3 cells in log phase growth to model aggressive, highly metabolically active prostate cancer were exposed to a gradually increasing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…In addition to identifying the minimal lethal temperature, we also investigated the effect of the combination of CA and chemotherapy for improving cancer kill. The use of adjuvants in combination with CA to sensitize cells in the ice ball periphery prior to or during a freezing event is an area of growing interest [32,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Given that cells within a frozen mass experience different rates of cooling and nadir temperatures based on proximity to a cryoprobe, maximizing the volume of complete cell death is imperative to procedure success.…”
mentioning
confidence: 99%
“…In addition to identifying the minimal lethal temperature, we also investigated the effect of the combination of CA and chemotherapy for improving cancer kill. The use of adjuvants in combination with CA to sensitize cells in the ice ball periphery prior to or during a freezing event is an area of growing interest [32,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Given that cells within a frozen mass experience different rates of cooling and nadir temperatures based on proximity to a cryoprobe, maximizing the volume of complete cell death is imperative to procedure success.…”
mentioning
confidence: 99%
“…These and other studies have detailed the benefi t of adjunctive treatment involving CA with the pre-treatment of low-dose chemotherapy, nutraceuticals or other agents in a number of cancers including prostate, breast, lung and liver among others [37,[65][66][67][68][69][70][71][72][73][74][75][76][77]. In vitro and in vivo studies involving prostate cancer have shown the ability of cryosensitizing adjuvants to elevate the minimal lethal temperature for hormone refractory prostate cancer from -40°C to -20°C via pre-treatment with sub-clinical (non-toxic) doses of 5-fl uorocil, taxotere and cisplatin [65,66,71].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies involving prostate cancer have shown the ability of cryosensitizing adjuvants to elevate the minimal lethal temperature for hormone refractory prostate cancer from -40°C to -20°C via pre-treatment with sub-clinical (non-toxic) doses of 5-fl uorocil, taxotere and cisplatin [65,66,71]. Other studies have demonstrated that combinatorial approaches using the active nutraceutical calcitriol (vitamin D 3 ) can result in the elevation of the minimal lethal temperature for prostate cancer to the -10 to -15°C range [57,75,76,78]. Based on these reports coupled with the identifi cation of a delayed molecular cell death response activated following freezing of C2 cells, the use of adjuvant agents, including chemotherapy and immunotherapy agents as well as RTK inhibitors, in combination with CA is an area that may also provide benefi t for treatment of MCT's and as such should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…When its active metabolite, calcitriol, is used with freezing of prostate cancer cells, freeze sensitivity increased to nadir temperatures as high as À5 C to À15 C regardless of the androgen sensitivity or rate of division (Ki67) of the prostate cancer [39][40][41][42]. This response is like other cancer types which carry the VD3 receptor such as breast [43][44][45], lung [46], colon [47,48] and pancreas [49] in addition to prostate ( Figure 4) [39][40][41][42]. The use of calcitriol as an adjunct as well as the VD3 receptor hypothesis is currently being tested in other cancers which do not contain the VD3 receptor, including bladder and liver cancer.…”
Section: Nutraceuticalsmentioning
confidence: 99%